Respostas

A melhor resposta!
2014-06-12T12:26:58-03:00
2m - 2 = 0 

2m = 2 

m = 2/2 

m = 1 => sua resposta 

Conferindo, 

A equação fica, 

5x ² + 3x = 0 

Colocando o x em evidência, 

x(5x + 3) = 0 

x ' = 0 

x " = ? 

5x " + 3 = 0 

5x " = - 3 

x " = - 3/5
3 4 3
2014-06-12T12:36:47-03:00
A = 5
b = 3
c = (2m - 2)

usando o produto das raízes....
produto= \frac{c}{a} \\\\x'~.~x''= \frac{c}{a} \\\\0~.~0= \frac{c}{a} \\\\ \frac{c}{a} =0\\\\ \frac{2m-2}{5} =0\\\\2m-2=0~.~5\\2m-2=0\\2m=2\\m= \frac{2}{2} \\\boxed{m=1}